Kontribusi Kepemimpinan Transformasi dan Komitmen Organisasi terhadap Kinerja Karyawan UMKM - Darma Rosmala Sari, Tri; Fernando, Yusra (E-Jurnal Akuntansi, 2021)
This study aims to provide guidelines for managers in improving the effectiveness of transformational leadership styles and organizational commitment. especially in UMKM. The research was conducted at MSMEs in Lampung. The research data were obtained through questionnaires distributed to MSME employees who have superior agro-industry and agribusiness products and analyzed using the Smart PLS application. The result of this research is that transformation leadership has a positive effect on employee performance. However, organizational commitment does not mediate the relationship between transformational leadership and employee performance and Transformational leadership has no positive effect on Organizational Commitment. This research can be used as a guideline for company managers / owners in improving the effectiveness of transformational leadership styles and organizational commitment within their business units. Keywords: Employee performance; Leadership Transformation; Organizational Commitment.